Transcriptome of the Southern Muriqui Brachyteles arachnoides (Primates:Platyrrhini), a Critically Endangered New World Monkey: Evidence of Adaptive Evolution - Moreira, Daniel A.; Lamarca, Alessandra P.; Soares, Rafael Ferreira; Coelho, Ana M. A.; Furtado, Carolina; Scherer, Nicole M.; Moreira, Miguel A. M.; Seuánez, Hector N.; Boroni, Mariana (Frontiers in Genetics, 2020)
The southern muriqui (Brachyteles arachnoides) is the largest-sized neotropical primate. This species is endemic to Brazil and is currently critically endangered due to its habitat destruction. The genetic basis underlying adaptive traits of New World monkeys have been a subject of interest to several investigators, with significant concern about genes related to the immune system. Without a reference genome, RNA-Seq and de novo transcriptome assembly have shown to be valuable genetic procedures for accessing gene sequences and testing evolutionary hypotheses. Here we first reported the sequencing, assembly, annotation and adaptive selection analysis for thousands of transcripts of B. arachnoides from two different tissues. More than 350 million reads from blood cells and fibroblasts RNA were generated by an Illumina HiSeq 2500 platform. We assembled 284,283 transcripts with N50 of 2,940 bp, with a high rate of complete transcripts, with a median high scoring pair coverage of 88.2%, including low expressed transcripts, accounting for 72.3% of complete BUSCOs. We could predict and extract 81,400 coding sequences with 79,8% of significant BLAST hit against the Euarchontoglires SwissProt dataset. From these 64,929 sequences, 34,084 were considered homologous to Supraprimate proteins, and from the remaining sequences (30,845), 94% were associated with a protein domain or a KEGG Orthology group, indicating potentially novel or specific protein-coding genes of B. arachnoides. Using a branch-site model, we searched for evidence of positive selection in 4,528 orthologous sets. This evolutionary analysis revealed 132 amino acid sites in 30 genes potentially evolving under positive selection, shedding light on primate genome evolution. These genes belonged to a wide variety of categories, including those encoding the innate immune system proteins (APOBEC3G, OAS2, CEACAM1) among others related to the immune response. This work generated a set of thousands of complete sequences that can be used in other studies of molecular evolution and may help to unveil the evolution of primate genes. Still, further functional studies are needed for understanding the underlying evolutionary forces modeling the primate genome.